INSTITUTE PRIESTHOOD CHEREMIS AND VOTYAK IN XVIII - BEGINNING OF XX CENTURY: TO THE PROBLEM OF COMPARISON AND CLASSIFICATION - R. A. Saberov; G. E. Shkalina (Вестник Мининского университета, 2017)
The article investigates the problem of fixing the priestly institution indigenous religions cheremis and votyaks domestic researchers XVIII - early XX centuries. Considered attempts to systematize and classify, construct hierarchies clergy studied ethnic groups by the scientific community. Based on a comparative analysis concludes functional similarity clergy, openness, availability of certain analogies in the systems considered religious institution. The author traces the presence of dissonance research in building systems priests associated with the lack of a unified approach to the study generated problems. Puts forward the assumption that the distribution of responsibilities between the ministers of religion, taking into account the location of the participants in supplications, is a certain image, a universal model, a figure resembling a branching "world tree".